(untitled) (ACS Publisher Books, 2022)
Math skills are so important and fun to teach to preschoolers. ‘My Activity – Maths Book’ is a quick preschool activity book to teach kids to identify numbers, count, and even colouring. • Perfect activity book for kids ages 2-5 • Full colourful pages • Hands-on activities to teach early math concepts • Charming pictures • Best for building fine motor and recognition skills • A great gift for toddlers Most suitable for early learners, this 32 pages book is a fun way to practice number recognition. Perfect age-appropriate activities will keep the tiny tots entertained for hours.